Mandibular ramus: A predictor for sex determination - A digital radiographic study - Kotya Naik Maloth; Vinay Kumar Reddy Kundoor; Sri Sai Lakshmi Preethi Vishnumolakala; Sunitha Kesidi; Modali Venkata Lakshmi; Moni Thakur (Wolters Kluwer Medknow Publications, 2017)
Aim: To evaluate mandibular ramus linear measurements on digital panoramic radiographs and to assess the usefulness of mandibular ramus in sex determination. Material and Methods: A retrospective study was conducted on 100 patients (50 males and 50 females) using digital panoramic radiographs of Khammam population with age ranging from 20 to 50 years. Standard digital panoramic radiographs were taken without any errors by Sirona, ORTHOPHOS XG 5 machine. The following five mandibular linear measurements were performed in cm such as upper ramus breadth, lower ramus breadth, condylar ramus height, projective ramus height, and coronoid ramus height. The obtained data were analyzed with the software SPSS 13.0 for statistical analysis using discriminate methods. Results: In the present study, all the linear measurements of mandibular ramus on digital panoramic radiographs showed a statistically significant difference between the genders. Conclusion: We conclude that the use of mandibular ramus is recommended as an aid for sex determination in forensic science due to their unique feature of sexual dimorphism.